A Survey of certain Mathematical Applications in Theoretical Physics: Exploring Mathematical Applications in Theoretical Physics (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Mathematics is a wonderful subject and an essential tool in physics, especially in theoreticalphysics, which relies heavily on mathematics (by which we mean here mainly Field Theory and HighEnergy Physics). Quantum Mechanics and Special Theory of Relativity are the foundations of these fieldsof physics, and numerous mathematical concepts are used in them. Differential geometry, infinite series,Mellin transforms, Fourier and integral transforms, special functions, calculus, complex algebra,topology, group theory, Riemannian geometry, functional analysis, linear algebra, and operator algebraare just a few of the topics we'll cover in this paper. Mathematical tools utilized in physics will also bediscussed in this course. It is not incorrect to state that mathematics is a powerful tool, without whichthere would be no Physics theory In addition, a brief summary of our research is given.